DOP21 Potential mechanisms linking biological therapies on SARS-CoV-2 susceptibility in Inflammatory Bowel Disease patients. (21st January 2022) - Pisani, L F; Mola, S; Crespi, G; Caprioli, F; Pastorelli, L; Annunziata, M L; Manfredi, M; Porta, C
Abstract: Background: The current novel coronavirus (SARS-CoV-2) pandemic is an ongoing global health crisis, which represents an important challenge for the whole society and mankind. Patients with inflammatory bowel disease (IBD) are treated with immunosuppressive drugs that are usually associated with more severe viral infections. However, the effects of the different therapies on the risk of SARS-CoV-2 infection and Covid-19 severity in IBD patients are still under investigation. Methods: Between April 2020 and April 2021, 238 IBD patients (N=145 with Crohn disease and N=93 with Ulcerative colitis) of the North Italy area have been enrolled. Both serum samples (N=238 IBD patients and N=45 healthy donors) and colon biopsies from inflamed and non-inflamed mucosa (N=88 IBD patients N=20 non-IBD control) have been collected. To evaluate the exposure to SARS-CoV-2, both clinical data and seroprevalence of anti-SARS-CoV-2 Ab have been analyzed. Serum samples were analyzed by untargeted metabolomics analysis and the frequency of a serum metabolomics signature associated with protection were evaluated in IBD versus healthy donors. Moreover, gene expression analysis of key proteins for virus entry (ACE2, TMPRSS2, TMPRSS4, ADAM17) were analyzed by qPCR in the gut mucosa biopsies of IBD patients. Results: The seroprevalence of anti-SARS-CoV-2 Ab in our cohort of IBD patients (10/238) indicates an overall lower incidence of COVID-19 in comparison with the general population of Lombardy. Accordingly, we observed that the serum metabolomics signature associated with protection was more frequent in IBD patients treated with anti-TNF (N=50, 70%), than healthy controls (N=45, 50%). Gene expression analysis of the proteins involved in SARS-CoV-2 entry also indicated that IBD patients treated with anti-TNF (N=14) had a lower mucosal level of SARS-CoV-2 receptor ACE2 and its sheddase ADAM17 than non-IBD subjects along with higher expression of the proteases TMPRSS2 and TMPRSS4. Moreover, vedolizumab-treated patients (N=7) showed a significant lower expression of ACE2, TMPRSS2 and TMPRSS4 than controls, whereas ADAM17 levels were similar. Conclusion: Our study indicates that IBD population treated with biologics has an overall lower risk to contract SARS-CoV-2 infection. Future studies to gather the mechanisms underpinning the effects of biologics on the expression of the proteins involved in SARS-CoV-2 viral entry in association with the specific metabolomics signature of viral susceptibility might shed light on potential targets to increase resistance in higher risk subgroups of patients.